THE INFLUENCE OF FUNDAMENTAL FACTORS ON STOCK PRICES IN THE JII 70 INDEX - Muhammad Arief Fathurrahman; Musviyanti Musviyanti (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
Muhammad Arief Fathurrahman. The Effect of Fundamental Factors on JII Sharia Stock Prices 70. Supervised by Ms. Musviyanti. This research was conducted to determine the effect of fundamental factors on Islamic stock prices in the JII 70 index. The proxies used are Return On Assets, Debt to Equity Ratio, Total Asset Turnover, Earning Per Share. The population in this study are companies listed as members of the JII 70 index on the Indonesia Stock Exchange during the 2018-2020 period. The sample selection in this study used purposive sampling, there were 38 companies that became the research sample. This study uses secondary data in the form of financial statements, annual reports, and stock data obtained from related companies and the Indonesian Stock Exchange. This study uses multiple regression analysis with the SPSS analysis tool version 25. The results of this study indicate that partially Return On Assets and Total Asset Turnover have a positive and significant effect on stock prices, while the Debt to Equity Ratio has a negative and significant effect on stock prices, Earnings Per Share has no effect on stock prices.